PENINGKATAN KUALITAS PENDIDIK DALAM MEMBANGUN SDM YANG UNGGUL SEBAGAI UPAYA MENYONGSONG KURIKULUM MERDEKA BELAJAR - Kastur, Annita; Hasanah, Isatul; Choir, Jihan Alhanin (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Advancing the education system is very important in creating a superior generation of nations. Changes that occur gradually in the scope of education are nothing but to change the mindset for the better. Especially in dynamic curriculum changes. This study aims to explain the improvement of the quality of educators in building superior human resources and the efforts of educators in welcoming the independent learning curriculum. This type of research is qualitative research using library research. The data analysis technique used is an analysis that has been obtained based on the literature used. The result of this research is the independent learning curriculum is an independent learning process. This means that students are free to think. The process aims so that students can choose the subjects they are interested in according to their abilities. However, this process must be carried out by an educator first. This is because educators are actors in advancing the education system. The efforts made by educators are to improve their competencies by participating in various pieces of training. Especially the free learning curriculum training. Educators also take teacher certification tests, improve academic qualifications, carry out development strategies, and make improvements in every lesson